2012
DOI: 10.5812/asjsm.34715
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural Power Dynamics and Coping Functions: A Narrative Case Report of a Female Paralympian

Abstract: Purpose: This case study explores the lived experiences of an elite female Paralympic powerlifting athlete. The focus is on restrictions and coping responses employed to manage the daily hassles within the cultural and ethnic requirements for achieving athletic excellence. Methods:With an unstructured interview, the narrative was acquired which ranged to a total of 75 minutes (approx) and 20 single spaced pages. The data was analyzed using Foucauldian discourse analysis in conjuncture to feminist poststructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies [ 32 , 33 ] explored the psychophysiological responses in PP. Da Silva et al [ 32 ] found that, in a sample of seven male athletes (aged 41.0 ± 10.1 years; body weight 84.7 ± 21.1 kg) undergoing a 4-week program of strength training, the increase in maximum dynamic strength ( p < 0.001; ES = 0.50) was paralleled by an increase in stress as measured by means of the “Recovery Stress Questionnaire for Athletes” (RESTQ-Sport) scales, with significant increases in the lack of energy ( p < 0.022; ES = 1.30), success ( p < 0.035; ES = 0.33), and sleep quality ( p < 0.007; ES = 0.62).…”
Section: Resultsmentioning
confidence: 99%
“…Ainda no século XXI, competições de alto rendimento e, principalmente, de desportos colectivos, são associadas a um estereótipo masculino, ligado à luta e confrontação (Marivoet, 2002), inclusive no campo paralímpico (Gomes et al, 2011;Roy, 2012). Porém, o processo de real igualdade de oportunidades de participação no campo desportivo ainda está longe de ser concluído.…”
Section: Cobertura Mediática Paralímpica Em Portugal | 143unclassified
“…Ainda que a perceção dos atletas deste estudo aponte para a tendência da igualdade de oportunidades na divulgação mediática entre homens e mulheres, e os dados da literatura sustentem o aumento da participação feminina (Brittain, 2010;Gomes et al, 2011), ainda existe uma série de barreiras culturais impostas por estereótipos de género no campo paralímpico, a necessitar de serem transpostas por mulheres atletas, a fim de conquistarem uma maior igualdade de condições de legitimação da sua participação desportiva (Howe, 2011;Roy, 2012).…”
Section: Cobertura Mediática Paralímpica Em Portugal | 143unclassified
“…This, associated with high training loads, tends to increase physical and psychological stress [8]. Given the few studies related to the modality and psychosocial indicators [33], the issue implies a problem in PP.…”
Section: Introductionmentioning
confidence: 99%